Implementasi Undang-Undang Nomor 26 Tahun 2007 tentang Penataan Ruang di Provinsi Aceh - Arnita Arnita; Fauzah Nur Aksa; Muhammad Hatta (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: The regulations on spatial planning in Qanun Aceh (local law in Aceh) is an important and a priority for areas that are prone to earthquake and former tsunami. This research aims to (a) know, somprehend and analyse the power of central government and local government in the planning matter in Aceh (b) to know, comprehend and analyse the legal drafting process of Qanun regarding the Planning in Aceh. This is descriptive analytical research by juridical normative approach by obtaining data from secondary data comprise of primary, secondary and tertiary legal sources. The data then are analysed qualitatively. The research is also conducted through socio legal approach by interview to complete secondary data. The research shows that firstly, the power of the government in the spatial planning inter districts or municipalities that is about planning, using, and controlling the space. The planning should not againts provincial planning, and the last should not against national spatial planning. Qanun Aceh is enacted in terms of running the Government and especially the autonomy, the assist duty and more elaborated in the act. The law is a rule enected both the house of repersentative and the head of executive either in provincial or regional level. The Implementation of the Act Number 26, 2007 on Spatial Planning in Aceh